Novel Wideband Metallic Patch Antennas with Low Profile - Zhong-Xiang Zhang; Meng Kong; Shuo Wang; Yong-Mei Pan (International Journal of Antennas and Propagation)
Two planar metallic patch (MP) antennas with low profiles are investigated and compared in this paper. The MP of each antenna consists of metallic patch cells and it is centrally fed by a rectangular slot. Two modes with close resonance frequencies are excited, providing a quite wide bandwidth. The antenna principle is explained clearly through a parametric study. Simulated and measured results show that the MP antennas with profile of 0.06λ0 can obtain a 10 dB impedance bandwidth of ~32% and an average gain of ~10 dBi.